PENGEMBANGAN MEDIA MIND MAP PADA MODEL PEMBELAJARAN ADVANCE ORGANIZER UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATERI PROTISTA - Rihana Wati; Ismail Ismail; Bunga Ihda Norra (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
Protista is material required interesting and effective media in learning in to obtain maximum learning outcomes. This study aims to determine the effect of developing mind map media on improving learning outcomes of class X MIPA students on protista material at SMA Negeri 1 Ulujami. This research was conducted online with the help of a google form in class X MIPA students. This research is a development research from Sivasailam Thiagarajan 4-D development, namely the Define, Design, Develop, and Disseminate stages. This research used Cluster Random Sampling technique. The data obtained consisted of observation data, validity test, questionnaires, student response questionnaires, pre-test and post-test results data in large group. The results of the assessment showed that the mind map media based on the advance organizer learning model is suitable for use in the learning process. Based on the feasibility an assessment by 76.47% of material experts, 89.01% of media expert, 95.2% of biology teacher, and 81% of students' respons. The effectiveness of students in learning with mind map media obtained a percentage of 62%, it means that the learning using mind map media is effective to improve student learning outcomes. The data analysis technique used the t-test and one-party hypothesis testing. The results of the t-test research showed that t count = 2.914 and t table = 1.7. The results showed t count> t table with α = 5%, so Ho was rejected and Ha was accepted. It means that the average understanding of the experimental class students was higher than the control class. The results of the normal gain test or the results of the increase in learning outcomes obtained an average of 0.62 which means that the increase in student learning outcomes is in the moderate criteria.        Materi protista memerlukan media menarik dan efektif dalam pembelajaran supaya diperoleh hasil belajar yang maksimal. Penelitian ini bertujuan untuk mengetahui pengaruh pengembangan media mind map terhadap peningkatan hasil belajar siswa kelas X MIPA pada materi protista di SMA Negeri 1 Ulujami. Penelitian ini dilaksanakan melalui daring dengan bantuan google form pada siswa kelas X MIPA. Penelitian ini merupakan penelitian pengembangan dari Sivasailam Thiagarajan pengembangan 4-D yaitu tahap Define, Design, Develop, and Disseminate. Teknik sampling yang digunakan dalam penelitian ini adalah teknik Cluster Random Sampling. Data yang diperoleh terdiri dari data observasi, angket uji validitas, angket tanggapan peserta didik dan data hasil pre-test dan post-test pada kelompok besar. Hasil penilaian menunjukan bahwa media mind map berbasis model pembelajaran advance organizer layak digunakan dalam proses pembelajaran. Kelayakan tersebut berdasarkan penilaian oleh ahli materi 76,47%, ahli media 89,01%, guru biologi 95,2%, dan tanggapan peserta didik 81%. Tingkat keefektifan peserta didik dalam pembelajaran dengan media mind map memperoleh persentase 62% yang artinya pembelajaran menggunakan media mind map efektif untuk meningkatkan hasil belajar peserta didik. Teknik analisis data menggunakan uji t-test dan uji hipotesis satu pihak. Hasil penelitian uji t-test diperoleh t hitung = 2,914 dan t tabel = 1,7. Hasil penelitian menunjukan t hitung > t tabel dengan α = 5% maka Ho ditolak dan Ha diterima artinya rata-rata pemahaman siswa kelas eksperimen lebih tinggi dari pada kelas kontrol. Hasil uji normal gain atau hasil uji peningkatan hasil belajar memperoleh rata-rata 0,62 yang berarti peningkatan hasil belajar peserta didik masuk kriteria sedang.